2009
DOI: 10.1007/s11367-009-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of wood-based heating in Norway

Abstract: Background, aim, and scope In this study, we evaluate the environmental effects of wood-based household heating. Wood is a significant source of household heating in Norway, and a comparative life cycle assessment of a wood-based heating system using an old and a modern stove was conducted to estimate the total life cycle benefits associated with the change from old to new combustion technology. Materials and methods The study uses a new approach to complete the inventory. Input-output data are used in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…For example, in a previous LCA study comparing the impact of modern vs old wooden ovens, the use phase was found to be responsible for over 60 % of the overall environmental impact (Solli et al 2009). However, the efficiency of burning stoves is greatly affected by the burning practice of users and the maintenance of the stove.…”
Section: Modeling Use Phase In Lca: Overview Of Current Practices Andmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a previous LCA study comparing the impact of modern vs old wooden ovens, the use phase was found to be responsible for over 60 % of the overall environmental impact (Solli et al 2009). However, the efficiency of burning stoves is greatly affected by the burning practice of users and the maintenance of the stove.…”
Section: Modeling Use Phase In Lca: Overview Of Current Practices Andmentioning
confidence: 99%
“…This underlies that changing the parametrization of user behavior would possibly lead to different impacts of the use phase. In the absence of any behavioral data on these parameters, emissions (e.g., impact) were calculated on the basis of an assumed efficiency (Solli et al 2009). However, the authors also acknowledge that the absolute levels of emissions are greatly sensitive to changes in efficiency.…”
Section: Modeling Use Phase In Lca: Overview Of Current Practices Andmentioning
confidence: 99%
“…This data can be interpreted as an indication: bioenergy already reached a certain degree of development and some research activities are now focusing on improving environmental performances of existing technologies. For instance, a recent paper compares wood combustion in new stoves for space heating with old stoves (Solli et al, 2009), while second generation bioethanol production from lignocellulosic sources are compared with first generation bioethanol from corn (Luo et al, 2009b;Williams et al, 2009). Some studies (13%) do not include a reference system in their assessment at all.…”
Section: Reference Systemmentioning
confidence: 99%
“…This approach takes into account all costs of operations, discounting the cost items, being particularly relevant to evaluate investments in capital-intensive firms, with significant presence of investment in buildings and plants, whose return on investment is in the long-run period. In addition, the LCC approach is considered of great importance for firms characterized by a high level of quality of production or, in the analysis of business efficiency, in terms of long-term quality (Hedeşiu et al, 2012;Kallunki and Silvola, 2008;Korpi and Ala-Risku, 2008;Schiffauerova and Dale, 2006;Srivastava, 2008), also taking into consideration aspects of the impact of the business social system and environment (Mizsey et al, 2009;Solli and Reenaas, 2009). This is the situation of companies in the Parma PDO ham sector that are often characterized by high investments in property and equipment.…”
Section: Methodsmentioning
confidence: 99%